The Impact of Yoga in Cancer Caregivers: A Review of Current Literature - Giridharan, S (International Research Journal of Ayurveda & Yoga, 2023)
This review explores yoga’s impact on cancer caregivers, focusing on mental health, stress, and quality of life. As crucial supporters of cancer patients, caregivers often face distress. Yoga shows potential in reducing stress and enhancing caregiver well-being. This study analyses yoga interventions to underscore their benefits in improving mental and physical health within cancer care.